PHYSIOLOGICAL PERFORMANCE OF CONVENTIONAL SOYBEAN CULTIVARS SEEDS AS A FUNCTION OF SIZE AND MOISTURE CONTENT DURING GERMINATION: Qualidade de sementes de soja - Sartori Dameto, Larissa; Krzyzanowski, Francisco Carlos; Eustáquio de Sá, Marco; Moreira, Adonis; Larissa Alexandra (REVISTA DE AGRICULTURA, 2023)
Quality test protocols for soybean seeds recommend a period of soaking and preconditioning without detailing the size of the seeds to be evaluated, as seeds of different sizes reach different degrees of humidity in each period owing to differences in their initial moisture level and size. Determining the degree of seed moisture during the preconditioning period is important when conducting accelerated aging, tetrazolium, and primary root protrusion tests. The objective of this study was to evaluate the physiological performance of two conventional soybean cultivars (BRS 284 and BRS 511) with three seed sizes (6.0, 6.5, and 7.0 mm) and three moisture levels, adjusted to 10%, 12%, and 14% and a control condition with 8.8% moisture. The experimental design was a randomized block scheme in a factorial arrangement of (3×3)+1 involving seed size and moisture. Regardless of the cultivar and moisture content, seeds with large diameters were more resistant to changes, such as accelerated aging, and resulted in larger seeds and higher numbers of developed seedlings than seeds with small diameters.